A feminist rewriting of Air India v Nergesh Meerza AIR 1981 SC 1829: proposal for a test of discrimination under Article 15(1). Issue 3 (2nd September 2021) - Atrey, Shreya; Pillai, Gauri
ABSTRACT: Nergesh Meerza is one of the earliest and most grave failures of the Supreme Court of India in the field of discrimination law. In a single stroke, not only did the Court drive a wedge between sex and gender to protect only the former from discrimination, it also debarred indirect and intersectional discrimination from the purview of the Constitution. This article presents a feminist judgment in this case which dissents from the original decision of the Court. It develops a version of constitutional protection from sex discrimination which embodies gender, indirect and intersectional discrimination. Importantly, it ventures into the hitherto neglected field of non-discrimination under Articles 15(1) and 16(2), and develops a substantive test for violations. Nergesh Meerza makes clear that without such a test, judges inevitably fail to give any meaning to the non-discrimination guarantees as part of the equality code of the Constitution.